(untitled) - Neil S Isaacs (London, 1995)
The book provides a comprehensive study of organic reaction mechanisms and the experimental techniques and logical connections used within organic chemistry. It covers the basics of the subject and the mechanisms for wide range of chemical reactions. It emphasizes the frontier orbital theory and the use of Huckel molecular orbitals to account for chemical reactivity. This is fully supported by references to the necessary experimental evidence, extensive data and new research methods currently in use
Keywords: physical organic chemistry